Ответы и объяснения

2014-01-28T11:19:05+00:00
3sin2x + Cos^x-sin^x -sin^2x-cos^2x=0
3sin2x + Cos^2x-sin^2x -sin^2x-cos^2x=0
3sin2x -sin^x -sin^2x=0
3sin2x -2Sin^2x=0
3sin2x -2Sin^x=0Извини,вот исправленный
2014-01-28T11:23:41+00:00
3sin^{2}x + cos^{2}x=1
6sinxcosx+cos^{2}x-sin^{2}x=1 // тут делим на сos^2x
6tgx+1-tg^{2}x=1
tg^{2}x-6tgx=0
tgx(tgx-6)=0
tgx=0                 или               tgx-6=0
x=πk, где k∈Z                        tgx=6
                                              x=arctg6+πk, k∈Z